2016
DOI: 10.1142/s0219749916400049
|View full text |Cite
|
Sign up to set email alerts
|

Classical emulation of a quantum computer

Abstract: This paper describes a novel approach to emulate a universal quantum computer with a wholly classical system, one that uses a signal of bounded duration and amplitude to represent an arbitrary quantum state. The signal may be of any modality (e.g. acoustic, electromagnetic, etc.) but this paper will focus on electronic signals. Individual qubits are represented by in-phase and quadrature sinusoidal signals, while unitary gate operations are performed using simple analog electronic circuit devices. In this mann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…This section shows an example bridging quantum and analog computing in showing an analog circuit model for quantum qubit computation (Figure 8). Quantum computing has been argued that could be performed through analog computing [44][45][46], have hypothesized parallels with op-amp circuits [47], that Z-valued algorithms cannot fully simulate a quantum computer [48], and an initial demonstration through a discrete benchtop analog circuit for a small quantum system (q-bits) utilizing sinusoidal input and output signals [49][50][51]. Typical quantum computing tends to be performed using fixed devices, such as qubits, and assume that the computation is instantaneous, effectively reaching its steady-state rapidly in the measurement timescales.…”
Section: Connecting Quantum Computing and Analog Computing Applicationsmentioning
confidence: 99%
“…This section shows an example bridging quantum and analog computing in showing an analog circuit model for quantum qubit computation (Figure 8). Quantum computing has been argued that could be performed through analog computing [44][45][46], have hypothesized parallels with op-amp circuits [47], that Z-valued algorithms cannot fully simulate a quantum computer [48], and an initial demonstration through a discrete benchtop analog circuit for a small quantum system (q-bits) utilizing sinusoidal input and output signals [49][50][51]. Typical quantum computing tends to be performed using fixed devices, such as qubits, and assume that the computation is instantaneous, effectively reaching its steady-state rapidly in the measurement timescales.…”
Section: Connecting Quantum Computing and Analog Computing Applicationsmentioning
confidence: 99%
“…The details of the hardware are described elsewhere [21]. Two of the five encoding qubits were represented in the frequency domain using signals with four narrowband tonals at ±1000 Hz and ±3000 Hz.…”
Section: Experimental Designmentioning
confidence: 99%
“…In a separate work, for example, we have shown how this mathematical connection can be leveraged to incorporate techniques developed for QEC to solve problems in digital wireless communications [20]. A prototype quantum emulation device (QED) that utilizes this embedding and physically performs the operations described in hardware has been developed and tested [21]. A natural question to ask given this device is whether it is possible to utilize techniques from QEC to enhance the performance of what is otherwise a purely classical analog device.…”
Section: Introductionmentioning
confidence: 99%
“…Each such projection may be formed from two single-qubit projections in a manner described above and will result in a set of three signals such that (16) and corresponding to the signal decomposition…”
Section: A Projectionsmentioning
confidence: 99%
“…Prior work has demonstrated that analog electronic signal processing can indeed provide a mathematically equivalent representation of a quantum computer and, therefore, provide an alternative physical implementation [15], [16]. This approach to quantum emulation uses the frequency domain of a signal to encode information, and approach we shall call frequency-based encoding.…”
Section: Introductionmentioning
confidence: 99%